Conference Review: Living History and Experimental Archaeology, Ukraine, March 2023 - Maria Ivantsiv (EXARC Journal, 2023)
The time of change, the time of choice came to Ukraine with the beginning of the war. We had to set vectors and priorities in all spheres of life. Science, culture and, in particular, open-air museums were no exception. First of all, we faced the issue of the protection and preservation of museum collections. Having adapted to the new conditions, the following questions arose: how to function in the future, how to develop and be interesting to visitors, and how to remain relevant and meet social demands. The need for a specialized event already existed long before the war. Thoughts about organizing a conference or summit in one format or another existed simultaneously in several persons, but due to insufficient communication it was not possible to implement the plans.